Citrus fruit : - Ladaniya, Milind S. (Elsevier, 2008)
The Book provides practical tips for post harvest management; Includes all aspects of citrus fruit biology, technology and quality evaluation; Discusses biotechnological applications and potential fresh citrus fruit quality improvement; Evaluates medicinal and therapeutic applications and recent clinical findings; Exhaustive glossary included